Incomplete ART adherence is associated with higher inflammation in individuals who achieved virologic suppression in the START study. Issue 6 (27th June 2019) - Castillo‐Mancilla, Jose R; Phillips, Andrew N; Neaton, James D; Neuhaus, Jacqueline; Sharma, Shweta; Baker, Jason V; Collins, Simon; Mannheimer, Sharon; Pett, Sarah; Touzeau‐Römer, Veronique; Polizzotto, Mark N; Lundgren, Jens D; et al.
Abstract: Introduction: Suboptimal ART adherence, despite HIV viral suppression, has been associated with chronic residual inflammation. Whether this association extends to individuals who initiate ART during early HIV infection remains unknown, which was the objective of this study. Methods: Plasma levels of interleukin‐6 (IL‐6), high‐sensitivity C‐reactive protein, serum amyloid A protein (SAA), IL‐27, soluble intercellular adhesion molecule‐1, soluble vascular adhesion molecule‐1, D‐dimer and the CD4+/CD8+ T‐cell ratio, were analysed at baseline and eight months after ART initiation in treatment‐naïve participants with HIV and CD4+ T‐cells >500 cells/mm 3 enrolled in the immediate arm of START. Adherence was assessed by seven‐day self‐report. Multivariable linear regression was utilized to analyse the association between ART adherence and each biomarker at the eight‐month visit in participants who achieved virologic suppression (<50 copies/mL). Results: We evaluated 1627 participants (422 female) who achieved virologic suppression at the eight‐month visit in the period between 2009 and 2013. Median (IQR) CD4+ T‐cell count before ART was 651 (585, 769) cells/mm 3 . Incomplete adherence was reported in 109 (7%) participants at the eight month visit. After adjusting for covariates, plasma IL‐6 was 1.12 (95% CI, 1.00 to 1.26; p = 0.047) fold higher in participants reporting incomplete versus 100% adherence. A similar association for SAA was observed in an exploratory analysis (1.29 (95% CI 1.04 to 1.60); p = 0.02). No significant differences in other biomarkers were observed. Conclusions: Incomplete ART adherence was associated with higher IL‐6 levels in individuals who achieved virologic suppression early after ART initiation in START. A potential similar association for SAA requires confirmation. These findings suggest a role for identifying strategies to maximize ART adherence even during virologic suppression. ClinicalTrials.gov number: NCT00867048.